1981
DOI: 10.1128/aac.20.4.463
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies of three antibiotic combinations against gram-negative bacteria and Staphylococcus aureus

Abstract: The activities of azlocillin, cefotaxime, and amikacin alone and in combination were evaluated in in vitro checkerboard studies, in infected neutropenic mice, and in human volunteers. The combination of cefotaxime plus amikacin was more synergistic in vitro than the others against the Enterobacteriaceae tested, and the combination of azlocillin plus amikacin was more synergistic against Pseudomonas aeruginosa and Staphylococcus aureus. Survival of neutropenic mice infected with Escherichia coli and Klebsiella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
5
24
1
Order By: Relevance
“…It is also possible that some of these isolates were from patients who had received these antibiotics for the treatment of pulmonary infections. Our results for azlocillin and amikacin alone and in combination are similar to those reported by Zinner et al against 39 strains of P. aeruginosa whose origin was not specified (19).…”
Section: Discussionsupporting
confidence: 81%
“…It is also possible that some of these isolates were from patients who had received these antibiotics for the treatment of pulmonary infections. Our results for azlocillin and amikacin alone and in combination are similar to those reported by Zinner et al against 39 strains of P. aeruginosa whose origin was not specified (19).…”
Section: Discussionsupporting
confidence: 81%
“…MICs for the various species were similar to those previously reported (4,14) and fit into the readily definable categories shown. The spectrum of azlocillin was complemented by the …”
supporting
confidence: 72%
“…Antagonism with azlocillin-cefotaxime was observed with 11% of the Enterobacteriaceae. [10][11][12]14). Although antagonism was not observed in the present study, it has been occasionally observed with both types of combinations against Enterobacteriaceae and P. aeruginosa (3,5,6,8,11,14).…”
mentioning
confidence: 38%
See 1 more Smart Citation
“…By the commonly used fractional inhibitory concentration index of .2.0 for antagonistic definition, the three moxalactam-amikacin studies show antagonism (10 (2,13,15,20). Moreover, synergy has proven to be valuable for the treatment of some infected patient populations, especially those with leukopenia and compromised immune mechanisms (12,20). It also seems critical to select the antimicrobial agents that are compatible in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%